Inhibitory Effects of Various Essential Oils and Individual Components against Extended-Spectrum Beta-Lactamase (ESBL) Produced by Klebsiella pneumoniae and Their Chemical Compositions - Orhan, Ilkay Erdogan; Ozcelik, Berrin; Kan, Yuksel; Kartal, Murat (Wiley, 2011)
In the current study, in vitro inhibitory activity of several essential oils obtained from the cultivated plants, Foeniculum vulgare, Mentha piperita and M. spicata, Ocimum basilicum, Origanum majorana, O. onites, O. vulgare, Satureja cuneifolia, and a number of individual essential oil components of terpene and aromatic types were screened against 10 isolated strains of Klebsiella pneumoniae producing extended-spectrum beta-lactamase (ESBL) enzyme, which makes this microorganism quite resistant against the antibiotics: trimetoprime-sulfametoksazol, sulbactam-ampicilin, clavulonate-amoxicilin, ceftriaxon, cefepime, imipenem, ceftazidime, tobramicine, gentamisine, ofloxacin, and ciprofloksasin. All of the essential oils and the components exerted a remarkable inhibition ranging between 32 and 64 mu g/mL against all of these strains as strong as the references (ampicilin and oflaxocin) inhibiting at 32 mu g/mL. Besides, chemical compositions of the essential oils were elucidated by gas chromatography-mass spectrometry (GC-MS). The essential oils and the pure components widely found in essential oils screened herein have shown remarkable inhibition against ESBL-producing K. pneumoniae strains, which leads to the suggestion that they may be used as food preservatives for this purpose.
Keywords: aromatic plants; ESBL; essential oil; GC-MS; Klebsiella pneumoniae